Counseling on ITE Law Violations in Using Social Media in Saragi Village, Buton Regency - Edy Nurcahyo; La Gurusi; Hadi Supriyanto; Kaswandi; La Ode Muhammad Karim; Zubair; Samsul; Afsalun Arman; Nanda Prastika; Revalina Nur Aliyah Priadi; Jusni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Legal counseling on violations of the ITE Law in using social media in the Saragi sub-district aims to create public awareness in social media wisely and avoid violations of the ITE Law. Forms of violation of the Information and Electronic Transaction Law in using social media have been regulated in Law no. 19 of 2016 Jo Law no. 11 of 2008 concerning Information and Electronic Transactions. Legal counseling on violations of the ITE Law in social media uses a statutory approach by first examining legal materials related to violations of the ITE Law in social media. Public awareness to be wise in using social media must always be increased in order to create social order in society.